Investigation and evaluation of H2S emissions from a municipal landfill - Vasarevičius, Saulius (Journal of Environmental Engineering and Landscape Management, 2011)
The aim of investigation was to evaluate the degree of pollution caused by a municipal landfill and determine the dependence of the amounts of emissions of the odorant hydrogen sulphide (H2S) on different parameters of the environment. The Jerubaičiai landfill in Plungė district was selected for the investigation. Measurements were recorded at 59 points and 2 monitoring wells. The measurement points and places were selected so that the landfill places generating the largest amounts of H2S and the directions of pollutant movement are identified. It was determined that the amounts of H2S varied from 0.9 ppm (in February) to 8.6 ppm (in August) in different places of the landfill. The largest amounts of H2S were identified in the areas of freshly-tipped waste. Odorants in these zones are generated during waste tipping out of trucks or waste pushing. H2S generation in the top layer of waste changes during the day and different seasons of the year. It is mainly influenced by air temperature. No dependence between H2S generation velocity and air humidity or pressure was identified. Article in English. Sieros vandenilio išsiskyrimo komunalinių atliekų sąvartyne tyrimai ir įvertinimas Santrauka. Tyrimų tikslas buvo įvertinti komunalinių atliekų sąvartyno skleidžiamą taršą ir nustatyti išsiskiriančio odoranto sieros vandenilio (H2S) kiekių priklausomumą nuo įvairių aplinkos parametrų. Tyrimams buvo pasirinktas Jerubaičių sąvartynas Plungės rajone. Matavimai atlikti 59 taškuose ir dviejuose monitoringo šuliniuose. Matavimo taškai ir vietos pasirinkta daugiausia H2S generuojančioms sąvartyno vietoms bei teršalų judėjimo kryptims nustatyti. Nustatyta, kad įvairiose sąvartyno vietose H2S kiekiai kinta nuo 0,9 ppm (vasario mėn.) iki 8,6 ppm (rugpjūčio mėn.). Didžiausi H2S kiekiai rasti ten, kur išpilamos naujai atvežamos atliekos. Šiose zonose odorantai išsiskiria sunkvežimiams išpilant atliekas ir jas stumdant.Per dieną ir įvairiais metų laikais viršutiniame atliekų sluoksnyje susidaro nevienodi H2S kiekiai. Didžiausią įtaką turi oro temperatūra. Priklausomybių tarp H2S susidarymo greičio ir oro drėgmės bei slėgio nenustatyta. Reikšminiai žodžiai: komunalinių atliekų tvarkymas, sąvartyno skleidžiama tarša, sieros vandenilis, aplinkos sąlygos. Исследования по оценке выбросов сернистого водорода на свалке муниципальных отходов Резюме. Целью исследования было оценить загрязнение окружающей среды, вызываемое муниципальными отходами на свалке, и определить зависимость количества выбрасываемого сернистого водорода (H2S) от условий окружаю щей среды. Исследования проводились на свалке Йерубайчай в районе Плунге. Измерения проводились в 59 точ ках и 2 колодцах мониторинга. Точки для измерений были подобраны таким образом, чтобы выявить зоны свалки с наибольшим количеством выбросов H2S. В ходе исследования установлено, что количество H2S меняется от 0,9 ppm (в феврале) дo 8,6 ppm (в августе). Наибольшие количества H2S найдены в местах выгрузки привозимых отходов. Выделение H2S из верхнего слоя отходов меняется в течение дня и в разное время года. Наибольшее влияние на выделение H2S оказывает температура воздуха. Зависимости между количеством выбрасываемого H2S и относительной влажностью или давлением воздуха не установлено. Ключевые слова: менеджмент муниципальных отходов, эмиссии загрязняющих веществ со свалок, сернистый водород, условия окружающей среды.